Effects of hemodialysis treatment on saliva flow rate and saliva composition during in-center maintenance dialysis: a cross-sectional study. Issue 1 (1st January 2021) - Yu, I-Chen; Liu, Chieh-Yu; Fang, Ji-Tseng
Abstract: Aim: To analyze changes in saliva flow rate and clinical measures from unstimulated whole saliva (UWS) among patients undergoing hemodialysis for end-stage kidney disease (ESKD). Background: Chronic hemodialysis causes changes in blood chemistry as well as dry mouth, due to removal of excess fluids. UWS is used to examine saliva flow rate as an indicator of mouth dryness. Whether UWS can be used to measure changes in clinical variables following hemodialysis has not been explored. Design: A cross-sectional quantitative study. Methods: Patients with ESKD were recruited by purposive sampling ( n  = 100) between 1 January and 30 June 2015 from a hospital in northern Taiwan. UWS was collected 1-hour pre-dialysis (T1), mid-dialysis (T2), and 1-hour post-dialysis (T3). Saliva flow rate and clinical variables were analyzed. Results: Saliva flow rate increased significantly from T1 to T3 (Wald χ 2  = 10.40, p  < .01). Changes in saliva from T1 to T3 included decreases in blood urea nitrogen and creatinine (Wald χ 2  = 97.12, p  < .001 and Wald χ 2  = 36.98, p  < .001, respectively). The pH and osmolality also decreased ( p  < .001 and p  < .01, respectively). Changes in electrolytes included decreases in potassium and calcium (Wald χ 2  = 6.71, p  < .05 and Wald χ 2  = 17.64, p  < .01, respectively) and increases in chloride (Wald χ 2  = 17.64, p  < .001). Conclusion: Our findings demonstrated saliva flow rate and several saliva components were altered during hemodialysis. The total volume of saliva secretion increased following dialysis, which can reduce xerostomia. Therefore, medical personnel could provide interventions of relieving dry mouth symptoms and increasing saliva flow rate before hemodialysis treatment.